The Repatriation of Polish Orphanages from USSR to Poland in 1946 - Światek, Lilianna (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The Committee for Polish Children in the USSR operated in the years 1943–1946. It was established on June 30, 1943 in Moscow following a political left-wing initiative. The Committee was a care-giving institution, fully in line with the Soviet system ideals. One of the most important matters tackled by the Committee was the repatriation of the youngest Polish citizens to their homeland. It was the subject of meetings, discussions and many hours of talks with the Soviet authorities. This issue was one of the most difficult tasks carried out by the Committee employees. The repatriation of orphanages to Poland lasted from January to August 1946.